Wasail al-Ma'rifah 'Inda Ibn Athaillah; al-Takamul bayna al-'Aql wa al-Qalb wa al-Asrar wa al-Anwar - Moh Isom Mudin (Tasfiyah: Jurnal Pemikiran Islam, 2018)
In this article, the author will discuss the ways to achieve knowledge according to Ibn Athaillah as-Sakandary. In sufism literature, revealed that the source of knowledge which is available in human beings according to the Sufis is qalb. Many researchers assume that they had reduced the role of mind in achieving knowledge. Therefore, Ibn Athaillah tries to integrate qalb and mind in achieving knowledge. Mind is an abstraction element to achieve knowledge which has a big role toward rational logic. The basic character of mind is active. Then, the method used by the mind is scientific reasoning and scientific experiments. On the contrary, the basic character of qalb is not active, but it is passive. The element of knowledge obtained by qalb is purely given by Allah. Therefore, to achieve knowledge, qalb uses intuitive witnessing (dzauq) method directly. Asrar or sir is tajally and witnessing media as the deepest element of qalb. Besides that, there are other powers available in human beings such as syu`aul bashirah, ‘ain al-bashirah, haqq al-bashirah. Those kinds of media are related to another term such as anwar. Some of these terms could complete each other.